Determinan Agresivitas Pajak: Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - St. Rohmawatik; Siti Sundari (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to test and analyze the influence of corporate social responsibility (CSR), capital intensity, and profitability on tax aggressiveness. This research uses quantitative methods with secondary data in the form of company annual reports. The population in this study were 99 mining companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling technique used a purposive sampling method and 15 companies were obtained as research samples with an observation period of 5 years, resulting in 75 analysis units. Technical data analysis uses structural equation models with WarpPLS 7.0 software. The research results show that capital intensity and profitability have an effect on tax aggressiveness, while CSR has no effect on tax aggressiveness in mining companies